Faunistic Composition and Ecological Distribution of Swallowtail Butterflies (Lepidoptera: Papilionidae) in Sarawak - Nurfarhannisa, Matchi (Universiti Malaysia Sarawak (UNIMAS), 2022)
Lepidoptera is known to be useful as environmental bio-indicators due to their sensitivity in sensing even minor changes in the environment. Thus, foundational knowledge obtained from data of past specimen collections is crucial. Results from this study showed there are 31 species of Papilionidae that were found in Sarawak based on the voucher specimens deposited at UNIMAS Insect Reference Collection (UIRC), Faculty of Resource Science and Technology, Universiti Malaysia Sarawak. Most of the species' ecological distribution is bound to the Mixed Dipterocarp Forest. Mixed dipterocarp forest sustains the greatest number of the Papilionidae species and individuals in Sarawak due to the ideal habitats and high abundance of larval host plants and food sources. There is a total of 38 species of swallowtail butterflies were recorded in Sarawak. This study reveals that the most abundant species is Papilio demoleus with 61 individuals and the least abundant species are Chilasa slateri hewitsoni, Graphium empedovana, G. stratiotes, G. eurypylus mecisteus, G. procles, Menelaides polytes, Lamproptera curius meges, L. curius curius, Papilio karna carnathus, P. nubilus nubilus and P. palinurus palinurus which is represented by singleton for each species.